Reliability of Pseudotyped Influenza Viral Particles in Neutralizing Antibody Detection - Yang, Jinghui (PLoS One, 2014)
BACKGROUND: Current influenza control strategies require an active surveillance system. Pseudotyped viral particles (pp) together with the evaluation of pre-existing immunity in a population might satisfy this requirement. However, the reliability of using pp in neutralizing antibody (nAb) detection are undefined. METHODOLOGY/PRINCIPAL FINDINGS: Pseudotyped particles of A(H1N1)pmd09 (A/California/7/2009) and HPAI H5N1 (A/Anhui/1/2005), as well as their reassortants, were generated. The reliability of using these pp in nAb detection were compared concurrently with the corresponding viruses by a hemagglutination inhibition test, as well as ELISA-, cytopathic effect-, and fluorescence-based microneutralization assays. In the qualitative detection on nAbs, the pp and their corresponding viruses were in complete agreement, with an R(2) value equal to or near 1 in two different populations. In the quantitative detection on nAbs, although the geometric mean titers (95% confidence interval) differed between the pp and viruses, no significant difference was observed. Furthermore, humoral immunity against the reassortants was evaluated; our results indicated strong consistency between the nAbs against reassortant pp and those against naïve pp harboring the same hemagglutinin. CONCLUSION/SIGNIFICANCE: The pp displayed high reliability in influenza virus nAb detection. The use of reassortant pp is a safe and convenient strategy for characterizing emerging influenza viruses and surveying the disease burden.